Screening chloroplast regions in Calophyllum brasiliense (Calophyllaceae) for suitability for population genetic analyses - Percuoco, Cecilia Beatriz (2018)
The uniparental inheritance and conserved structure of the chloroplast genome among many angiosperms makes it suitable for constructing gene lineages and inferring population histories based on these relationships. However, the analysis of a single chloroplast region to solve population issues has not yielded the desired amount of variability due to the low mutation rate. Therefore, it is necessary to screen and carefully analyze chloroplast intergenic or intronic regions to select the most appropriate for studying the genetic variability in the chloroplast genome of a particular taxon. In this context, the aim of this work was to characterize 8 regions in Calophyllum brasiliense using 11 selected primer pairs and to evaluate their usefulness for phylogeographic analysis. Intergenic spacers petA-psbJ, petG-trnP and rpl32-trnL and the trnL intron demonstrated potentially informative sites. The combination of these 4 regions will allow the analysis of genetic population structure and the integration of historical aspects to inform strategies for conserving C. brasiliense, especially for highly impacted populations and those at risk of local extinction.